2014
DOI: 10.5812/ijem.13633
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity in Patients With Type 2 Diabetes Mellitus in Yemen

Abstract: Background:Obesity is common in type 2 diabetic patients in some of the Middle Eastern countries, which are amongst the countries with highest rates of diabetes mellitus and obesity.Objectives:We conducted this study to assess the prevalence of obesity in Yemeni patients with type 2 diabetes mellitus.Patients and Methods:Body mass index (BMI) of patients with type 2 diabetes mellitus who were 25-years-old or older was measured during their first visit to an endocrinology and diabetes clinic in Sana’a, Yemen ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
18
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 21 publications
10
18
2
Order By: Relevance
“…Generally, the study observed high prevalence (85.0%) of overweight/obesity among type 2 diabetic patients who were attending care clinics in these setting. This finding is in line with those reported from both population and facility-based studies conducted in Saudi Arabia [15, 19, 20], United States [21], United Kingdom [14], Nepal [22], Iran [23], Yemen [16] and Ghana [17]. High prevalence of overweight and obesity in this setting might be explained by the urbanisation, globalisation of food production and marketing, adoption of western culture and development of infrastructure that enhances little physical activities to our patients.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, the study observed high prevalence (85.0%) of overweight/obesity among type 2 diabetic patients who were attending care clinics in these setting. This finding is in line with those reported from both population and facility-based studies conducted in Saudi Arabia [15, 19, 20], United States [21], United Kingdom [14], Nepal [22], Iran [23], Yemen [16] and Ghana [17]. High prevalence of overweight and obesity in this setting might be explained by the urbanisation, globalisation of food production and marketing, adoption of western culture and development of infrastructure that enhances little physical activities to our patients.…”
Section: Discussionsupporting
confidence: 92%
“…Generally study observed high prevalence of (81.3%) of overweight/obesity among type 2 diabetic patients who were attending care clinics in these setting. This finding is in line with those reported from both population and facility-based studies conducted in Saudi Arabia [13][14][15], United States [16], United Kingdom [17], Iran [18], Yemen [19], and Ghana [20]. The research found higher prevalence of overweight or obesity in female participants as compared to their male's counterparts i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Diabetes is accompanied by a wide range of complications, for instance, cardiovascular disease, retinopathy, nephropathy, and neuropathy (Girach & Vignati, ; Tripathi & Srivastava, ). Previous studies reported that most patients with diabetes are overweight or obese (Al‐Sharafi & Gunaid, ; Mugharbel & Al‐Mansouri, ; Thomas, Zimmet, & Shaw, ). Obesity is a key component in the pathophysiology of diabetes and development of complications and exerts its effect through insulin resistance, excessive oxidative stress, and impaired metabolic regulation (Al‐Goblan, Al‐Alfi, & Khan, ; Van Gaal & De Block, ; Van Gaal, Mertens, & Christophe, ).…”
Section: Introductionmentioning
confidence: 99%